Characterization of two GH5 endoglucanases from termite microbiome using synthetic metagenomics - Ben Guerrero, Emiliano (2020)
Here, we characterize two novel GH5 endoglucanases (GH5CelA and GH5CelB) from an uncultured bacterium identified in termite gut microbiomes. Both genes were codon-optimized, synthetized, cloned, and expressed as recombinant proteins in Escherichia coli for subsequent purification. Both enzymes showed activity on the pNPC and barley β-glucan substrates, whereas GH5CelB also showed low activity on carboxymethyl cellulose. The optimum conditions for both enzymes were an acid pH (5) and moderate temperature (35 to 50 °C). The enzymes differed in the kinetic profiles and patterns of the generated hydrolysis products. A structural-based modeling analysis indicated that both enzymes possess a typical (β/α)8-barrel fold characteristic of GH5 family, with some differential features in the active site cleft. Also, GH5CelB presents a putative secondary binding site. Furthermore, adjacent to the active site of GH5CelA and GH5CelB, a whole subdomain rarely found in GH5 family may participate in substrate binding and thermal stability. Therefore, GH5CelA may be a good candidate for the production of cello-oligosaccharides of different degrees of polymerization applicable for feed and food industries, including prebiotics. On the other hand, GH5CelB could be useful in an enzymatic cocktail for the production of lignocellulosic bioethanol, because of the production of glucose as a hydrolysis product.